2021
DOI: 10.1186/s12911-021-01458-1
|View full text |Cite
|
Sign up to set email alerts
|

A method for interoperable knowledge-based data quality assessment

Abstract: Background Assessing the quality of healthcare data is a complex task including the selection of suitable measurement methods (MM) and adequately assessing their results. Objectives To present an interoperable data quality (DQ) assessment method that formalizes MMs based on standardized data definitions and intends to support collaborative governance of DQ-assessment knowledge, e.g. which MMs to apply and how to assess their results in different si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Although 40, 31, and 31% of respondents indicated an absence of policies that support data quality assessment, interoperability and sharing respectively in their institutions, 52, 44, and 39%, respectively, do not know whether their institution has any of these policies. These are in line with the results of recent studies (e.g., Bian et al, 2020;Tute et al, 2021) who found that data quality dimensions of assessment for accuracy, completeness, conformance and plausibility, interoperability, and reuse are limited in practice across disciplines.…”
Section: Institutional Policies That Support Data Management and Sharingsupporting
confidence: 91%
“…Although 40, 31, and 31% of respondents indicated an absence of policies that support data quality assessment, interoperability and sharing respectively in their institutions, 52, 44, and 39%, respectively, do not know whether their institution has any of these policies. These are in line with the results of recent studies (e.g., Bian et al, 2020;Tute et al, 2021) who found that data quality dimensions of assessment for accuracy, completeness, conformance and plausibility, interoperability, and reuse are limited in practice across disciplines.…”
Section: Institutional Policies That Support Data Management and Sharingsupporting
confidence: 91%
“…Comprehensive organizational structures have been established including data stewards for modeling clinical concepts of a domain, responsible parties for each source system, and a data reviewing board for overall, regular analysis of data sets. The in-house development openCQA [6] makes commonly governed compilations (e.g. for reports or dashboards) of various data quality indicators applicable on HiGHmed's technical architecture.…”
Section: Resultsmentioning
confidence: 99%
“…We used the open source tool openCQA ([ 11 , 27 ] commit c0a8a784 from 2021-02-19) for DQA. We generated simple MMs based on variables’ datatypes calculating results per patient and per site.…”
Section: Methodsmentioning
confidence: 99%
“…A knowledge base (applicable compilation of MMs for a certain task, cf. [ 11 ]) considering this derived DQA-knowledge could for example include an MM that lists all patients without blood pressure values (Additional file 4 : Appendix D shows an example of such a MM for openCQA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation